Surgical Clipping of Previously Coiled Recurrent Intracranial Aneurysms: A Single-Center Experience - Zheng, Yongtao; Zheng, Lili; Sun, Yuhao; Lin, Dong; Wang, Baofeng; Sun, Qingfang; Bian, Liuguan (Frontiers in Neurology, 2021)
Objective: This study reviews our experiences in surgical clipping of previously coiled aneurysms, emphasizing on recurrence mechanism of intracranial aneurysms (IAs) and surgical techniques for different types of recurrent IAs. Method: We performed a retrospective study on 12 patients who underwent surgical clipping of aneurysms following endovascular treatment between January 2010 and October 2020. The indications for surgery, surgical techniques, and clinical outcomes were analyzed. Result: Twelve patients with previously coiled IAs were treated with clipping in this study, including nine females and three males. The reasons for the patients having clipping were as follows: early surgery (treatment failure in two patients, postoperative early rebleeding in one patient, and intraprocedural aneurysm rupture during embolization in one patient) and late surgery (aneurysm recurrence in five patients, SAH in one, mass effect in one, and aneurysm regrowth in one). All aneurysms were clipped directly, and coil removal was performed in four patients. One patient died (surgical mortality, 8.3%), 1 patient (8.3%) experienced permanent neurological morbidity, and the remaining 10 patients (83.4%) had good outcomes. Based on our clinical data and previous studies, we classified the recurrence mechanism of IAs into coil compaction, regrowth, coil migration, and coil loosening. Then, we elaborated the specific surgical planning and timing of surgery depending on the recurrence type of IAs. Conclusion: Surgical clipping can be a safe and effective treatment strategy for the management of recurrent coiled IAs, with acceptable morbidity and mortality in properly selected cases. Our classification of recurrent coiled aneurysms into four types helps to assess the optimal surgical approach and the associated risks in managing them.